Pollination ecology of Syagrus smithii (Arecaceae), a palm with cantharophily from Colombian Amazon - Guerrero-Olaya, Nilson Y. (2017)
From the evaluation floral morphology, reproductive phenology, floral biology, floral visitors and pollinator’s definition, the reproduction strategy of a Syagrus smithii (Arecaeae) in a Colombian Amazonia region was described. Syagrus smithii palms grow up to 10 m high and produce one to three bisexual inflorescences. The bisexual inflorescences bear staminate and pistillate flowers arranged in triads with a female central flower and two male sides. The inflorescences are protandric and open during daytime, remaining active for 28 days. The male phase extends for the first 14 days, which are followed by 10 days of an inactive phase; the pistillate phase lasts up to four days. The inflorescences of S. smithii were visited by 37 species of insects belonging to the orders Coleoptera, Hymenoptera and Diptera. All visitors get to the flowers in searching of abundant pollen, floral tissues that feed them and as sites of reproduction. The most effective pollinators of S. smithii were Mystrops sp nov. 2 and Mystrops sp nov. 3 (Nitudiladae: Coleoptera), and Microstates sp.2 and Sibinia sp. 1 (Curculionidae: Coleoptera) were secondary pollinators. Since all species of major pollinators have developed their life cycles into inflorescences, we suggest the existence of a specialized system and mutual dependence between pollinators and the palm, which ensures the presence of pollinators throughout the year and individuals with viable seeds.